Perencanaan Perbaikan Proses Administrasi dan Analisis Kebutuhan Operator Proses Produksi PG 1160 di PT E-T-A Indonesia - Chokro, William; Sutapa, I Nyoman (Jurnal Titra, 2013)
PT E-T-A Indonesia had problems on administrations and production process. In the administrations, it was found that the lead time to fulfill the customer order was too long. While, in the production process, the company wanted to know how many workers should be utilized in the production line. To answer these problems, we occupied Makigami Diagram for identifying inefficiency processes in the administration department. We also measured the daily KPI for deciding the optimized the number of workers. As the results of those improvement; the total day for administration process was reduced to two days and the number of workers could be reduced up to two persons.